(untitled) - Purcell, Steven W. (Rome, 2012)
Sea cucumbers are exploited and traded in more than 70 countries worldwide. This book provides identification information on 58 species of sea cucumbers that are commonly exploited in artisanal and industrial fisheries around the world. It is intended for fishery managers, scientists, trade officers and industry workers. The volume is fully indexed and contains an introduction, a glossary, and a dedicated bibliography.
Keywords: Hải sâm,Sea cucumbers